Assessing the Socioeconomic Impacts of Land Tenure Systems Across Different Regions - Naveen Sharma; Vijay Kumar (International Journal of Land, 2025)
Land tenure systems are fundamental in shaping the socioeconomic structure and dynamics of communities across the globe. These systems, which define the legal and customary relationship between individuals, groups, and the land they own, use, or occupy, hold significant implications for economic development, social equity, and environmental sustainability. They determine how land resources are accessed, managed, and transferred, thereby influencing economic activities, wealth distribution, and community stability. This article provides a comprehensive assessment of the socioeconomic impacts of various land tenure systems observed in different regions worldwide, emphasizing their role in economic growth and development. It delves into how formal land tenure systems, characterized by legally recognized land rights, as well as informal or customary systems, shaped by traditional practices and local agreements, affect individuals and communities in different regions. Additionally, this study examines the effect of these tenure systems on resource accessibility, especially in rural areas where land is the primary source of livelihood. The article also highlights the crucial role governance structures play in shaping land tenure security, including the effectiveness of land administration, enforcement of land laws, and the recognition of informal land rights. Furthermore, the paper underscores the interplay between formal and informal tenure systems, which can sometimes complement or conflict with each other, affecting land use, agricultural productivity, and community relations. Finally, it discusses the implications of these varied land tenure systems for policy formulation, particularly in developing countries, where land-related issues such as disputes, land tenure insecurity, and unequal land distribution are prevalent. The article concludes by exploring potential policy solutions aimed at improving land tenure security, promoting inclusive development, and fostering sustainable land management practices.
Keywords: Formal and informal tenure; Land rights and equity; Land tenure systems; Socioeconomic impacts; agricultural productivity; land governance